Pelatihan Teknik Menulis Artikel dan Publikasi untuk Mahasiswa - Rafika Sari; Reny Aziatul Pebriani (Universitas Muhammadiyah Semarang, 2025)
Scientific writing and publication skills are essential competencies for university students to support their academic and professional development. However, many students face challenges such as limited understanding of article structure, writing techniques, and the publication process in scientific journals. This article aims to describe a community service initiative in the form of a workshop on scientific writing and publication, specifically designed for students. The workshop was intended to enhance students' capacity to produce scientific papers that meet academic standards and to understand the publication process. The implementation methods included theoretical lectures, interactive discussions, and practical writing sessions with intensive mentoring by experienced speakers. The materials covered the structure of scientific articles, techniques for constructing logical arguments, strategies for journal selection, and steps for responding to the peer-review process. The evaluation results showed a significant improvement in participants’ understanding and writing skills. Moreover, the workshop increased students’ confidence to initiate the publication of their scientific work in national and international journals. This article concludes that workshops on scientific writing and publication can serve as an effective community service model to foster a writing culture, enhance academic productivity, and improve the quality of university graduates.